Vaccinia virus viability under different environmental conditions and different disinfectants treatment - Shan Mei; Liang Wei; Yu Xie; Fei Zhao; Yu Huang; Zhangling Fan; Yamei Hu; Liming Wang; Lingwa Wang; Ying Wang; Fengwen Xu; Fei Guo (Elsevier, 2024)
Monkeypox (mpox) outbreak in 2022 has caused more than 91,000 cases, has spread to 115 countries, regions, and territories, and has thus attracted much attention. The stability of poxvirus particles in the environment is recognized as an important factor in determining their transmission. However, few studies have investigated the persistence of poxviruses on material surfaces under various environmental conditions, and their sensitivity to biocides. Here, we systematically measured the stability of vaccinia virus (VACV) under different environmental conditions and sensitivity to inactivation methods via plaque assay, quantitative real-time polymerase chain reaction (qPCR), and Gaussia luciferase (G-luciferase) reporter system. The results show that VACV is stable on the surface of stainless steel, glass, clothing, plastic, towel, A4 paper, and tissue and persists much longer at 4 °C and −20 °C, but is effectively inactivated by ultraviolet (UV) irradiation, heat treatment, and chemical reagents. Our study raises the awareness of long persistence of poxviruses in the environment and provides a simple solution to inactivate poxviruses using common disinfectants, which is expected to help the control and prevention of mpox virus and future poxvirus outbreaks.